Analisis Kinerja Keuangan Koperasi Republik Indonesia (KPRI) Kantor Kementerian Agama Kabupaten Gresik Tahun 2018-2020 - Latifah Wulandari, Fanny; Yasin, Ach (Universitas Negeri Surabaya, 2022)
This study was conducted to determine the financial performance of the Republic of Indonesia Cooperative (KPRI) Makmur Office of the Ministry of Religious affairs of Gresik Regency in 2018-2020 using financial ratio analysis. In this research, the data used primary data and secondary data obtained based on the financial statements of KPRI Makmur in 2018 - 2020. Data analysis used descriptive quantitative method, which is studied using financial ratio analysis (Liquidity Ratio, Profitability Ratio, & Solvency Ratio) based on the Decree of the State Minister of Cooperatives & KUKM No.06/Per/M/KUKM/V/2006 concerning health assessment standards. The following is the calculation of the Liquidity Ratio (Current Ratio = 2018 as much as 403.10%, in 2019 as much as 344.64%, & in 2020 as much as 236.78%), Profitability Ratio (Return on Asset = year 2018 as much as 4.61%, in 2019 as much as 3.06%, & in 2020 as much as 2.60%), (Return on Equity = 2018 as much as 9.59%, in 2019 as much as 5. 96%, & in 2020 as much as 4.64%), & Solvency Ratio (Debt to Asset Ratio = 2018 as much as 51.98%, in 2019 as much as 48.58%, & in 2020 as much as 43.92%). From the study result, there was a decrease every year. Profitability Ratio showed the output of the ROA analysis was incuded in the criteria quite good & the output of the ROE analysis is included in the criteria was not good. Because the capital invested in KPRI Makmur wouldn’t made SHU as a result, the resulting output decreases in the output of profit (profit) obtained when measured according to KPRI Makmur's capital. However, the Liquidity & Solvency Ratio in KPRI Makmur was included by great criteria.